2016
DOI: 10.1002/2016ja023117
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between magnetosonic waves and ring current protons: Gyroaveraged test particle simulations

Abstract: Gyroaveraged test particle simulations are implemented to quantitatively investigate interactions between linearly polarized magnetosonic waves (i.e., equatorial noises) and ring current protons inside and outside the plasmasphere at L = 4.5. For magnetosonic waves at the frequency of 33.3 Hz (fw/fcp = 6.4 at the magnetic equator, for L = 4.5), it is found that wave‐particle interactions at the resonance order corresponding to the lowest resonant proton energy (i.e., N = 6) are dominant. The interactions at ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 59 publications
0
35
0
1
Order By: Relevance
“…Recent studies further stated that scattering by MS waves can provide an efficient mechanism for energetic electron diffusion in the slot region and outer radiation belt and primarily account for the formation of electron butterfly or top‐hat distributions in the inner magnetosphere (Li, Ni, et al, ; Li, Bortnik, et al, ; Ni et al, ; Xiao, Yang, et al, ). In addition, Fu et al () found that MS waves can potentially accelerate ring current protons at a few keV inside the plasmasphere and at ~10 keV outside the plasmasphere.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies further stated that scattering by MS waves can provide an efficient mechanism for energetic electron diffusion in the slot region and outer radiation belt and primarily account for the formation of electron butterfly or top‐hat distributions in the inner magnetosphere (Li, Ni, et al, ; Li, Bortnik, et al, ; Ni et al, ; Xiao, Yang, et al, ). In addition, Fu et al () found that MS waves can potentially accelerate ring current protons at a few keV inside the plasmasphere and at ~10 keV outside the plasmasphere.…”
Section: Introductionmentioning
confidence: 99%
“…Although fast magnetosonic (MS) waves can also affect the ring current ions and the radiation belt electrons (Fu et al, ; Horne et al, ; Li, Ni, et al, ; Li et al, ; Ma et al, ; Xiao et al, ), their responses to the magnetospheric compression and expansion are not clear so far. MS waves are almost linearly polarized and propagate nearly perpendicular to the ambient magnetic field (Chen & Thorne, ; Russell et al, ; Santolík et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, numerous studies have found that these emissions are able to produce electron butterfly distributions via Landau resonance and bounce resonance energization (Horne et al, ; Shprits, ; Bortnik and Thorne, ; Li JX et al, ; Li LY et al, ; Ni BB et al, , ; Tao X and Li X, ; Xiao FL et al, ). On the other hand, MS waves are also found capable of interacting with protons through cyclotron resonance (Xiao FL et al, ; Fu S et al, ). However, the interaction between MS waves and protons has drawn much less attention.…”
Section: Introductionmentioning
confidence: 99%
“…Based on quasi‐linear theory, Xiao FL et al () proposed that MS wave‐induced proton precipitation is a potential mechanism accounting for the proton aurora. Recently, the test particle simulations by Fu S et al () indicated that MS waves have the ability to accelerate ring current protons both inside and outside the plasmasphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation